Planning and Performance of Dynamic Experiments with the AVR Power Plant - Wimmers, M.; Pohl, P. (Nuclear science and engineering, 1987)
In collaboration with Kernforschungsanlage Jülich, Federal Republic of Germany, and other companies, dynamic experiments have been carried out with the Arbeitsgemeinschaft Versuchsreaktor (AVR) to test advanced dynamic computer models with the goal of using low-enriched uranium (LEU) fuel in future high-temperature gas-cooled reactors. Since LEU fuel has been used for the AVR since 1982, both experimental and theoretical behavior has been studied during the changeover from highly enriched uranium to LEU. The experiments comprise fast power transients that are initiated by either a fast control rod movement or a fast change of coolant flow. The neutron flux and other important parameters are registered in suitable time expansion. To prevent the cantilevered segments of the carbon brick core ceiling from being exposed to unallowable high-temperature gradients, the rod movements are restricted to limit the reactivity variation to ∼ 60 mNile. For the coolant flow transients, the blower speed is usually reduced from 100 to 50%, and then elevated again to 80% after 30 min. A return to 100% is not possible because of the overshoot of the neutron flux. Also, in some experiments the speed is reduced to 80%, after which the core remains under the control of xenon influence for ∼1 day.